2020
DOI: 10.1002/erv.2789
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise‐based interventions in patients with anorexia nervosa: A systematic review

Abstract: Objective This study aimed to conduct a systematic review of research that has evaluated the outcomes of exercise‐based interventions in anorexia nervosa (AN) patients. Method We searched for studies in the MEDLINE, Embase, Web of Science, PsycInfo, Scopus and SPORTDiscus databases. We followed Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines throughout the selection process, and used Cochrane tools to assess the risk of bias in the primary studies. In cases where sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…On the other hand, muscle strength and endurance increased significantly in the trunk and limbs. Our results are difficult to compare with those of other studies due to different activities performed in populations of anorexic subjects of different ages and BMIs [47]. Only two medical teams were interested in developing strength during a physical activity program in anorexic patients [11,43,44].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, muscle strength and endurance increased significantly in the trunk and limbs. Our results are difficult to compare with those of other studies due to different activities performed in populations of anorexic subjects of different ages and BMIs [47]. Only two medical teams were interested in developing strength during a physical activity program in anorexic patients [11,43,44].…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have already shown that it is possible to perform physical activities for anorexic subjects while gaining weight or improving BMI [ 42 , 43 , 44 , 45 , 46 ]. However, no difference has been found compared to control anorexic subjects not performing physical activity [ 47 ]. Body fat increase had already been shown in patients with anorexia from Australia aged from 16 to 19 years old (BMI from 14.8 to 15.4 kg/m 2 ) who gained between 2.5 and 8% of body fat while they performed various anaerobic and aerobic physical activities [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, some ET programs have been developed within specialized units for ED to promote better adherence to treatment and achieve more effective and sustainable reductions in the main symptoms of AN and associated disorders ( 17 , 32 , 34 ). Even if this remains a minority and no official recommendations exist, the development of ET in standard care is a growing phenomenon ( 32 , 35 ). Achamrah et al’s ( 32 ) review and Bratland-Sanda’s et al ( 34 ) publication both reported that different types of ET, including aerobic exercise, resistance exercise, and mind–body PE (MBPE), have been implemented for patients with AN and other ED.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated the impact of ET interventions on AN patients and shown positive effects on the main symptoms of the disease, and physical and mental health, as well as better behavior toward the health care team ( 32 , 35 ). However, to our knowledge, there are still few studies assessing the effects of ET interventions in patients with AN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation